IMPLEMENTASI MANAJEMEN RISIKO DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH DR. R. SOEDJATI SOEMODIARDJO PURWODADI GROBOGAN - Toyo, Eleonora Maryeta; Maryana, Mega; Suwarni, Sri; Rustaman, Heri; Susilawati, Linda (Jurnal Farmasi & Sains Indonesia, 2022)
Risk is a state of uncertainty and can be measured quantitatively. Every service activity in the Pharmacy Installation contains risk. Risk management is a process of identifying, measuring, analyzing, and handling risks that may arise during service delivery. The implementation of risk management is expected to reduce and or eliminate losses incurred for the continuity of health services. This study aims to determine the implementation of risk management in the Pharmacy Installation of the Regional General Hospital Dr. R. Soedjati Soemodiardjo Purwodadi Grobogan. This research is a non-experimental research with descriptive method, namely retrospective data collection with total sampling technique. Samples were taken from the Quality Control Agency at the Regional General Hospital Dr. R. Soedjati Soemodiardjo Purwodadi Grobogan in the January-December 2020 period. The data obtained were tabulated, presented, and reported in percentage form for further qualitative and quantitative analysis. From the research results obtained, it is known that the most common type of incident is KPC in the prescription service category. This is influenced by factors including human resources, infrastructure, standard operating procedures, and formularies. The implementation of Risk Management in the Pharmacy Installation of the Regional General Hospital Dr. R. Soedjati Soemodiardjo Purwodadi Grobogan is still not effective, because it still experiences obstacles in several stages of the Risk Management process.